Large, infected Cowper's syringoceles: a rare cause of perineal sepsis in adult men. Issue 12 (7th December 2022) - Adasonla, Kelvin; Pathak, Sandeep; Li, Chi-Ying
Abstract: Urologists and general surgeons alike are familiar with assessing acute perineal pathology. A Cowper's gland syringocele is a rare cystic dilatation of the male bulbourethral gland, typically seen in children. We report the diagnosis and emergency management of two adult cases of large, infected Cowper's gland syringoceles. A comorbid 76-year old was diagnosed with sepsis and penile swelling, but there was no discrete superficial pathology. Magnetic resonance imaging (MRI) revealed a perineal collection communicating with the membranous urethra. A suprapubic catheter was inserted, and aspiration was attempted. Meanwhile, a 55-year-old diabetic presented with severe perineal pain. MRI revealed a deep perineal collection, involving the scrotum and proximal penis. He improved with antibiotics and aspiration of the collection. This rare diagnosis may be more common in older men than previously thought. Pelvic MRI is a key diagnostic tool. A minimally invasive approach is possible in those with considerable perioperative risk.